THEORIES OF ADOLESCENT SUBSTANCE USE AND ABUSE - Brandt, CJ; Delport, CSL (Social Work/Maatskaplike Werk, 2005)
This article reviews nine different theories regarding adolescent subtance use and abuse. Amongst these theories the following are emphasised: (a) substance specific cognitives (b) social learning processes, (c) commitment to conventional values and (d) intra-personal processes. Some similarities and differences among these theories as well as the conceptual boundaries of each theory are addressed. In order to integrate these theories and to explain the etiology of youth substance use and abuse, a framework or model is presented to the reader.